2022
DOI: 10.1186/s12889-022-14431-y
|View full text |Cite
|
Sign up to set email alerts
|

What predicts people’s belief in COVID-19 misinformation? A retrospective study using a nationwide online survey among adults residing in the United States

Abstract: Background Tackling infodemics with flooding misinformation is key to managing the COVID-19 pandemic. Yet only a few studies have attempted to understand the characteristics of the people who believe in misinformation. Methods Data was used from an online survey that was administered in April 2020 to 6518 English-speaking adult participants in the United States. We created binary variables to represent four misinformation categories related to COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 60 publications
0
3
1
Order By: Relevance
“…Nevertheless, despite their understandable frustration with the chaotic information landscape during the pandemic, many participants demonstrated remarkable resilience in the face of the widespread misinformation. In contrast to past research that suggests demographic factors such as older age, low-income, and belonging to a minority race/ethnicity are associated with a higher tendency to consume and believe in misinformation [24,25], the narratives presented in this study show otherwise. Many participants were aware of current issues, able to discern inaccurate information, and even took further steps to inform others.…”
Section: Discussioncontrasting
confidence: 99%
“…Nevertheless, despite their understandable frustration with the chaotic information landscape during the pandemic, many participants demonstrated remarkable resilience in the face of the widespread misinformation. In contrast to past research that suggests demographic factors such as older age, low-income, and belonging to a minority race/ethnicity are associated with a higher tendency to consume and believe in misinformation [24,25], the narratives presented in this study show otherwise. Many participants were aware of current issues, able to discern inaccurate information, and even took further steps to inform others.…”
Section: Discussioncontrasting
confidence: 99%
“…The Japanese media have also highlighted the importance of debunking SARS-CoV-2 misinformation online such as the belief that vaccination can lead to infertility in women, that the vaccination will make the recipient sick as it contains an active coronavirus, or that the vaccines have not been comprehensively tested due to the speed at which they were developed [97]. It is apparent that SARS-CoV-2 misinformation affects audiences and demographics differently, underscoring the need to customize communication strategies and messaging for specific populations [98].…”
Section: Vaccine Hesitancy and Susceptibility To Sars-cov-2 Misinform...mentioning
confidence: 99%
“…However, data simultaneously show high levels of belief in vaccine-related misinformation, even among those who have completed the primary inoculation series [ 2 , 3 ]. Despite concerted efforts on the part of public health experts to counter the spread of viral misinformation [ 4 , 5 ], recent survey data suggest that several false narratives about the constitution and efficacy of COVID-19 vaccines have persisted in spite of significant scientific evidence proving their effectiveness [ 3 , 6 ]. While health officials have emphasized the importance of ongoing vaccine boosters in maintaining immunity against SARS-CoV-2 infections [ 7 ] – and prior research has found trust in health information to be a critical determinant of booster shot acceptance [ 8 , 9 ] – it remains unclear if or to what extent belief in misinformation affects the willingness of previously vaccinated individuals to accept regular COVID-19 booster shots.…”
Section: Introductionmentioning
confidence: 99%